Engine Cooling Compressor Vibration Analysis on the Vessel Binama 07 Jakarta - Haris, Dendi; Tumpu, Mula (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
This study aims to analyze the vibration levels of the refrigeration compressor on the fishing vessel Binama 07 Jakarta to evaluate operational conditions and detect potential component failures. Measurements were conducted using a vibration meter in three directions horizontal, vertical, and axial and a digital tachometer to determine the engine’s rotational speed in RPM. The assessment refers to ISO 20816-3:2022, a standard used to classify the condition of rotating industrial machinery. Vibration data collected from November 3–23, 2024, showed that most values fell within Zone B (acceptable), while some reached Zone C (not recommended for long-term operation). Only two days, November 12 and 23, recorded values in Zone A (good), with a vibration level of 1.6 mm/s. No data fell into Zone D (dangerous), indicating no signs of extreme vibration. However, consistent readings in Zone B and occasional spikes into Zone C suggest early signs of machine condition degradation. These findings have significant implications for the performance of the ship’s cooling system, as excessive vibration can affect the stability of the storage temperature for the catch. In the fishing industry, unstable temperatures can directly impact product quality and market value. Therefore, regular vibration monitoring is recommended as a predictive maintenance strategy to maintain optimal performance of the refrigeration system on fishing vessels.